High‐dose chemotherapy and autologous bone marrow or stem cell transplantation versus conventional chemotherapy for women with early poor prognosis breast cancer - Farquhar, Cindy (Cochrane Database Syst Rev, 2016)
BACKGROUND: Overall survival rates are disappointing for women with early poor prognosis breast cancer. Autologous transplantation of bone marrow or peripheral stem cells (in which the woman is both donor and recipient) has been considered a promising technique because it permits use of much higher doses of chemotherapy. OBJECTIVES: To compare the effectiveness and safety of high‐dose chemotherapy and autograft (either autologous bone marrow or stem cell transplantation) with conventional chemotherapy for women with early poor prognosis breast cancer. SEARCH METHODS: We searched the Cochrane Breast Cancer Group Specialised Register, MEDLINE (1966 to October 2015), EMBASE (1980 to October 2015), the World Health Organization's International Clinical Trials Registry Search Platform, and ClinicalTrials.gov on the 21 October 2015. SELECTION CRITERIA: Randomised controlled trials (RCTs) comparing high‐dose chemotherapy and autograft (bone marrow transplant or stem cell rescue) versus chemotherapy without autograft for women with early poor prognosis breast cancer. DATA COLLECTION AND ANALYSIS: Two review authors selected RCTs, independently extracted data and assessed risks of bias. We combined data using a Mantel‐Haenszel fixed‐effect model to calculate pooled risk ratios (RRs) and 95% confidence intervals (CIs). We assessed the quality of the evidence using GRADE methods. Outcomes were survival rates, toxicity and quality of life. MAIN RESULTS: We included 14 RCTs of 5600 women randomised to receive high‐dose chemotherapy and autograft (bone marrow transplant or stem cell rescue) versus chemotherapy without autograft for women with early poor prognosis breast cancer. The studies were at low risk of bias in most areas. There is high‐quality evidence that high‐dose chemotherapy does not increase the likelihood of overall survival at any stage of follow‐up (at three years: RR 1.02, 95% CI 0.95 to 1.10, 3 RCTs, 795 women, I² = 56%; at five years: RR 1.00, 95% CI 0.96 to 1.04, 9 RCTs, 3948 women, I² = 0%; at six years: RR 0.94, 95% CI 0.81 to 1.08, 1 RCT, 511 women; at eight years: RR1.17, 95% CI 0.95 to 1.43, 1 RCT, 344 women; at 12 years: RR 1.18, 95% CI 0.99 to 1.42, 1 RCT, 382 women). There is high‐quality evidence that high‐dose chemotherapy improves the likelihood of event‐free survival at three years (RR 1.19, 95% CI 1.06 to 1.34, 3 RCTs, 795 women, I² = 56%) but this effect was no longer apparent at longer duration of follow‐up (at five years: RR 1.04, 95% CI 0.99 to 1.09, 9 RCTs, 3948 women, I² = 14%; at six years RR 1.04, 95% CI 0.87 to 1.24, 1 RCT, 511 women; at eight years: RR 1.27, 95% CI 0.99 to 1.64, 1 RCT, 344 women; at 12 years: RR 1.18, 95% CI 0.95 to 1.45, 1 RCT, 382 women). Treatment‐related deaths were much more frequent in the high‐dose arm (RR 7.97, 95% CI 3.99 to 15.92, 14 RCTs, 5600 women, I² = 12%, high‐quality evidence) and non‐fatal morbidity was also more common and more severe in the high‐dose group. There was little or no difference between the groups in the incidence of second cancers at four to nine years' median follow‐up (RR 1.25, 95% CI 0.90 to 1.73, 7 RCTs, 3423 women, I² = 0%, high‐quality evidence). Women in the high‐dose group reported significantly worse quality‐of‐life scores immediately after treatment, but there were few statistically significant differences between the groups by one year. The primary studies were at low risk of bias in most areas, and the evidence was assessed using GRADE methods and rated as high quality for all comparisons. AUTHORS' CONCLUSIONS: There is high‐quality evidence of increased treatment‐related mortality and little or no increase in survival by using high‐dose chemotherapy with autograft for women with early poor prognosis breast cancer.